Lithium-supplementing positive electrode material as well as preparation method and application thereof

The lithium-supplemented cathode material with in-situ compounded lithium particles and carbon coating addresses the issues of poor contact and gas generation in lithium-ion batteries, enhancing conductivity and performance.

CN119208777AInactive Publication Date: 2024-12-27BYD CO LTD

Patent Information

Application Number
CN202411337178.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing lithium supplementation methods for positive electrodes in lithium-ion batteries result in poor contact between the lithium supplement agent and the active material particles, leading to high decomposition voltage, gas generation, and increased risk of side reactions, especially in high-temperature environments.

Method used

A lithium-supplemented cathode material is developed with in-situ compounded lithium particles on the core of the positive electrode active material, coated with carbon, to improve electronic and ionic conduction, reduce decomposition voltage, and minimize gas generation.

Benefits of technology

The solution effectively reduces the risk of gelation, enhances conductivity, and improves cycle and rate performance of the battery by stabilizing the lithium-supplemented particles and reducing water absorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208777A_ABST
    Figure CN119208777A_ABST
Patent Text Reader

Abstract

The invention provides a lithium-supplementing positive electrode material and a preparation method and application thereof, the lithium-supplementing positive electrode material comprises an active material core and a coating layer coating the surface of the active material core, and the coating layer comprises lithium-supplementing particles and carbon; the active material inner core comprises one or more of LixFeyPO4 and LiFezMn1-zPO4, x is more than or equal to 0.9 and less than or equal to 1.1, y is more than or equal to 0.9 and less than or equal to 1.1, and 0 lt; zlt, zlt; 1; the lithium supplement particles comprise LiaMbOc, M is selected from one or more of Fe, Mn, Ni, Zr, Co, Cr and Cu, a is greater than 0 and less than or equal to 6, b is greater than 0 and less than or equal to 3, and c is greater than 0 and less than or equal to 5. The lithium-supplementing positive electrode material can effectively reduce the risk of a gel phenomenon of positive electrode active slurry, can improve the electron conduction capability and the ion conduction capability of the positive electrode active slurry, can effectively solve the problem of gas production in the later use process of a battery, and further improves the rate capability and the cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the technical field of lithium-ion batteries, and in particular to a lithium-supplemented cathode material, a preparation method thereof, and an application thereof. Background Art

[0002] The lithium supplementation technology is an effective means to improve the energy density of lithium-ion batteries, while improving the battery cycle life and energy storage performance. The commonly used existing lithium supplementation technologies include negative electrode lithium supplementation, positive electrode lithium supplementation, electrolyte lithium supplementation, separator lithium supplementation, current collector lithium supplementation, and electrochemical lithium supplementation. Among them, positive electrode lithium supplementation is one of the most commonly used means. Currently, the method for positive electrode lithium supplementation is usually to directly add a lithium supplement agent to the positive electrode slurry during the homogenization process. This will result in poor contact between the lithium supplement agent and the positive electrode active material particles, leading to a high decomposition voltage, and further resulting in problems such as gas generation in the battery after lithium supplementation; moreover, the lithium supplement agent residues in a high oxidation state remaining inside the positive electrode sheet contacting the electrolyte will increase the risk of side reactions, and further increase the risk of gas generation in the battery during use, especially in a high-temperature environment. Summary of the Invention

[0003] In view of this, the present application provides a lithium-supplemented cathode material, a preparation method thereof, and an application thereof. By in-situ compounding lithium-supplemented particles on the core of the positive electrode active material, the size of the lithium-supplemented particles in the lithium-supplemented cathode material is much smaller than that of the lithium supplement agent conventionally added to the positive electrode active slurry. Furthermore, it can effectively reduce the risk of gelation of the positive electrode active slurry caused by residual alkali on the surface of the lithium supplement agent, and can effectively improve the electronic conduction ability and ionic conduction ability of the lithium-supplemented cathode material. Moreover, the carbon-containing coating layer can effectively slow down the rate of water absorption and failure of the lithium-supplemented particles. In addition, the structure of the lithium-supplemented cathode material can also effectively reduce the decomposition voltage, thereby solving the problem of gas generation in the later use process of the battery, and further improving the rate performance and cycle performance of the battery.

[0004] The first aspect of the present application provides a lithium-supplemented cathode material, which includes an active material core and a coating layer coated on the surface of the active material core. The coating layer includes lithium-supplemented particles and carbon; the active material core includes one or more of Li x Fe y PO4 and LiFe z Mn 1-z PO4, where 0.9 ≤ x ≤ 1.1, 0.9 ≤ y ≤ 1.1, 0 < z < 1; the lithium-supplemented particles include Li a M b O c , where M is selected from one or more of Fe, Mn, Ni, Zr, Co, Cr, and Cu, 0 < a ≤ 6, 0 < b ≤ 3, 0 < c ≤ 5.

[0005] In the embodiment of the present application, the carbon is coated on the surface of the active material core and / or the surface of the lithium supplement particle.

[0006] In an embodiment of the present application, at least part of the lithium supplement particles are in-situ grown on the surface of the active material core.

[0007] In an embodiment of the present application, the mass ratio of the lithium supplement particles to the active material core is (0.1-10):100.

[0008] In the implementation manner of the present application, the mass percentage of the carbon in the lithium-supplementing positive electrode material is 0.1%-5%.

[0009] In the embodiment of the present application, the particle size of the active material core is 0.1 μm-15 μm; the particle size of the lithium supplement particle is 0.1 μm-12 μm.

[0010] In the embodiment of the present application, the specific surface area of ​​the lithium-supplementing positive electrode material is 3m 2 / g-20m 2 / g.

[0011] The second aspect of the present application provides a method for preparing the lithium-supplemented positive electrode material provided in the first aspect, comprising:

[0012] Mixing a lithium source, a phosphorus source, an iron source, a carbon source and an M metal source to obtain a lithium-supplementing positive electrode material precursor; or, mixing a lithium source, a phosphorus source, an iron source, a carbon source, a manganese source and an M metal source to obtain a lithium-supplementing positive electrode material precursor;

[0013] The lithium-supplementing positive electrode material precursor is sintered in stages to obtain the lithium-supplementing positive electrode material.

[0014] In the embodiment of the present application, the staged sintering includes a first sintering treatment and a second sintering treatment performed sequentially; the sintering temperature of the first sintering treatment is 450℃-750℃, and the sintering time is 3h-18h; the sintering temperature of the second sintering treatment is 750℃-1000℃, and the sintering time is 4h-36h; the temperature of the second sintering treatment is higher than the temperature of the first sintering treatment.

[0015] In an embodiment of the present application, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium hydroxide monohydrate, lithium nitrate, lithium oxide, lithium peroxide and lithium acetate.

[0016] In an embodiment of the present application, the phosphorus source includes one or more of lithium dihydrogen phosphate, iron phosphate, ammonium phosphate, sodium dihydrogen phosphate, lithium monohydrogen phosphate, lithium phytate and sodium tripolyphosphate.

[0017] In an embodiment of the present application, the iron source includes one or more of ferrous oxide, ferrous oxide, ferric nitrate, ferric phosphate, ferrous oxalate and ferrous sulfate.

[0018] The carbon source includes one or more of sugars, high molecular organic matter, and conductive carbon, and the carbon source specifically includes one or more of glucose, sucrose, fructose, chitosan, lignin, carboxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, phenolic resin, needle coke, petroleum coke, pitch coke, asphalt, polystyrene, polyphenylene vinylene, carbon black, acetylene black, super-P, carbon nanotubes, graphene, Ketjen black, and vapor-grown carbon fiber;

[0019] The manganese source includes one or more of manganese tetraoxide, manganese sulfate, manganese oxalate, manganese carbonate, manganese dioxide and manganese acetate.

[0020] The third aspect of the present application also provides a positive electrode sheet, which includes a current collector and a positive electrode active layer loaded on the current collector, and the positive electrode active layer includes the lithium-supplementing positive electrode material provided in the first aspect or the lithium-supplementing positive electrode material prepared by the preparation method provided in the second aspect.

[0021] A fourth aspect of the present application provides a lithium-ion battery, which includes the positive electrode sheet provided in the third aspect of the present application.

[0022] A fifth aspect of the present application provides an electrical device, which includes a lithium-ion battery as provided in the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 A schematic diagram of the cross-sectional structure of a lithium-supplementing positive electrode material provided in one embodiment of the present application;

[0024] Figure 2 This is a schematic diagram of the cross-sectional structure of a lithium-supplementing positive electrode material provided in yet another embodiment of the present application.

[0025] Description of Figure Numbers

[0026] 100-lithium-supplemented positive electrode material; 101-active material core; 102-lithium-supplemented particles; 103-carbon. DETAILED DESCRIPTION

[0027] The present application is further described in detail below in conjunction with preferred embodiments, but the protection scope of the present application is not limited to the following specific embodiments.

[0028] In the present application, all professional terms have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present application.

[0029] Lithium supplementation technology is an effective means to improve the energy density of lithium-ion batteries while enhancing the battery cycle life and energy storage performance. Commonly used existing lithium supplementation technologies include lithium supplementation at the negative electrode, lithium supplementation at the positive electrode, lithium supplementation in the electrolyte, lithium supplementation on the separator, lithium supplementation on the current collector, and electrochemical lithium supplementation. Among them, lithium supplementation at the positive electrode is one of the most commonly used means. Currently, the method of lithium supplementation at the positive electrode usually involves directly adding a lithium supplement agent to the positive electrode slurry during the homogenization process. This results in poor contact between the lithium supplement agent and the positive electrode active material particles, leading to a relatively high decomposition voltage, and further causing problems such as gas generation in the battery after lithium supplementation. Moreover, the residue of the lithium supplement agent in the positive electrode sheet, which is in a highly oxidized state, coming into contact with the electrolyte increases the risk of side reactions, and further increases the risk of gas generation in the battery during use, especially in a high-temperature environment.

[0030] To address the above problems, the present application provides a lithium-supplemented positive electrode material, its preparation method, and application. The lithium-supplemented positive electrode material can effectively reduce the risk of gelation of the positive electrode active slurry caused by residual alkali on the surface of the lithium supplement agent by in-situ compounding lithium supplement particles on the core of the positive electrode active material. It can also effectively improve the electron conduction ability and ion conduction ability of the lithium-supplemented positive electrode material, and the carbon-containing coating layer can effectively slow down the rate of water absorption and inactivation of the lithium supplement particles. In addition, the structure of the lithium-supplemented positive electrode material can effectively solve the problem of gas generation during the later use of the battery, thereby improving the rate performance and cycle performance of the battery.

[0031] See Figure 1 , the present application provides a lithium-supplemented positive electrode material 100, which includes an active material core 101 and a coating layer covering the surface of the active material core 101. Among them, the coating layer includes lithium supplement particles 102 and carbon 103. In the embodiments of the present application, the active material core 101 includes Li x Fe y PO4 and LiFe z Mn 1-z PO4, one or more of them, where 0.9 ≤ x ≤ 1.1, 0.9 ≤ y ≤ 1.1, 0 < z < 1. In some specific embodiments, x can be, for example, 0.9, 0.95, 1, 1.05, 1.1; y can be, for example, 0.9, 0.95, 1, 1.05, 1.1; z can be, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9. In the embodiments of the present application, the lithium supplement particles 102 include Li a M b O c, wherein M is selected from one or more of Fe, Mn, Ni, Zr, Co, Cr and Cu, 0<a≤6, 0<b≤3, 0<c≤5. In some specific embodiments, a can be, for example, 1, 2, 3, 4, 5, 6; b can be, for example, 0, 1, 2, 3; c can be, for example, 1, 2, 3, 4. The lithium-supplementing positive electrode material of the present application provides a lithium-supplementing function by in-situ compounding the lithium-supplementing particles with the core of the positive electrode active material without affecting the energy density of the core of the active material 101. Compared with the commonly used lithium replenishment method of directly adding the lithium replenisher to the active slurry, the lithium replenishment particles 102 are compounded with the active material core 101 in an in-situ growth manner, which can effectively improve the contact between the lithium replenishment particles 102 and the active material core 101. On the one hand, it can effectively reduce the decomposition voltage required for decomposition polarization, effectively avoid the gas production problem of the battery during the cycle use, and reduce the risk of iron melting of the residue after the decomposition of the lithium replenishment particles, thereby improving the service life and safety performance of the battery. On the other hand, it can effectively shorten the electron transmission path and the lithium ion transmission path, and improve the electron conductivity and ion conductivity of the lithium replenishment positive electrode material 100. In addition, the present application uses lithium-rich metal oxides as lithium replenishment particles, which will release some oxygen or oxygen free radicals during the decomposition and replenishment process, which can improve the low-temperature performance of the battery and reduce its impedance to a certain extent. In addition, the coating layer containing carbon 103 at least partially wraps the lithium-replenishing particles 102, which can to a certain extent isolate the lithium-replenishing particles 102 from the external environment, thereby effectively reducing the risk of gelation of the positive electrode active slurry caused by residual alkali on the surface of the lithium-replenishing particles. At the same time, it can also shield the lithium-replenishing particles from the invasion of moisture in the environment, effectively slowing down the rate of water absorption and failure of the lithium-replenishing particles 102, thereby broadening the application scenarios of lithium-replenishing positive electrode materials and reducing production costs.

[0032] In the embodiment of the present application, at least part of the lithium supplement particles 102 are in-situ grown on the surface of the active material core 101. In the present application, in-situ growth means that under the condition of primary sintering, the lithium supplement particles 102 are distributed around the active material core 101 and are physically close to the active material core 101, and the lithium supplement particles 102 and the active material core 101 form secondary particles.

[0033] In some embodiments of the present application, the structure of the lithium-supplemented positive electrode material 100 is as follows Figure 1As shown, it includes an active material core 101, lithium supplement particles 102 bonded to the surface of the active material core 101, and a carbon coating layer 103 coated on the surface of the active material core 101 and / or the surface of the lithium supplement particles 102, wherein the lithium supplement particles 102 are in-situ grown on the surface of the active material core 101. In some embodiments of the present application, the lithium supplement particles 102 are in direct contact with the surface of the active material core 101. The lithium supplement particles in the lithium supplement positive electrode material of this structure are larger in size, thereby making the specific surface area of ​​the lithium supplement positive electrode material smaller and the stability of the lithium supplement positive electrode material better.

[0034] In some other embodiments of the present application, the structure of the lithium-supplemented positive electrode material 100 is as follows: Figure 2 As shown, it includes an active material core 101 and a coating layer coated on the surface of the active material core 101, wherein the coating layer includes lithium supplement particles 102 and carbon 103, and the lithium supplement particles 102 are distributed inside the coating layer formed by the carbon 103. In some embodiments of the present application, the lithium supplement particles 102 are not in direct contact with the surface of the active material core 101, and the lithium supplement particles 102 are connected to the surface of the active material core 101 through the carbon 103.

[0035] In the embodiment of the present application, carbon 103 is coated on the surface of the active material core 101 and / or the lithium supplement particles 102. In the embodiment of the present application, the coating of the active material core 101 and the lithium supplement particles 102 by carbon 103 can be complete or incomplete. The lithium supplement positive electrode material 100 of the present application effectively reduces the contact area between the lithium supplement particles 102 and the air through the coating of carbon 103, thereby reducing the rate of water absorption failure of the lithium supplement particles 102 and effectively avoiding the residual alkali on the surface of the lithium supplement particles and the positive electrode active slurry to mix and form agglomeration, gelation, etc., thereby improving the utilization rate and service life of the lithium supplement particles, reducing the cost of preparation, and further improving the electrochemical performance of the battery product. The coating of carbon 103 can also optimize the conductive network structure of the positive electrode lithium supplement material, ensure the electronic path of the lithium supplement particles 102 and the active material core 101, and improve the lithium supplement efficiency of the lithium supplement particles 102 while ensuring the conductivity of the lithium supplement positive electrode material 100. In addition, it can also improve the lithium supplement particles 102 and the lithium ion deintercalation path of the active material core 101, improve the ion conductivity of the lithium supplement positive electrode material 100, and thus improve the comprehensive electrochemical performance of the battery. And through the coating of carbon 103, the active material core 101 and the lithium supplement particles 102 are more closely combined, and the electrochemical environment around the residues after the lithium supplement particles are charged and decomposed is more stable, which is conducive to suppressing the iron melting phenomenon, thereby improving the safety of the lithium supplement positive electrode material.

[0036] In the embodiment of the present application, the mass ratio of the lithium supplement particles 102 and the active material core 101 is (0.1-10): 100. In some specific embodiments, the mass ratio of the lithium supplement particles 102 and the active material core 101 can be, for example, 0.1: 100, 0.2: 100, 0.3: 100, 0.5: 100, 0.8: 100, 1: 100, 2: 100, 3: 100, 4: 100, 5: 100, 6: 100, 7: 100, 8: 100, 9: 100, 10: 100. The present application can make the lithium supplement positive electrode material have a higher specific capacity while improving the utilization rate of the lithium supplement particles by controlling the mass ratio of the lithium supplement particles and the active material core within a suitable range, effectively avoiding the waste of the lithium supplement particles while avoiding the side reactions caused by the excessive amount of lithium supplement particles, so that the lithium supplement positive electrode material has better comprehensive performance and meets the application requirements of different scenarios.

[0037] In the embodiment of the present application, the mass percentage of carbon 103 in the lithium-supplementing positive electrode material 100 is 0.1%-5%. In some specific embodiments, the mass percentage of carbon 103 in the lithium-supplementing positive electrode material 100 can be, for example, 0.1%, 0.2%, 0.3%, 0.5%, 0.6%, 0.8%, 1%, 2%, 3%, 4%, 5%. The present application can control the thickness of the coating layer by reasonably controlling the carbon content in the lithium-supplementing positive electrode material, and can also comprehensively adjust the coating method and degree of carbon 103 for the active material core 101 and the lithium-supplementing particles 102, thereby regulating the power performance, cycle performance and storage performance of the battery to meet the different needs of the battery.

[0038] In the embodiment of the present application, the particle size of the active material kernel 101 is 0.1μm-15μm. In some specific embodiments, the particle size of the active material kernel 101 can be, for example, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.8μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 8μm, 10μm, 12μm, 15μm. In some embodiments of the present application, the particle size of the active material kernel 101 is 0.1μm-10μm. In some embodiments, the particle size of the active material kernel 101 is 0.2μm-5μm. In the embodiment of the present application, the particle size of the active material kernel 101 can be the particle size of the primary particles, or the particle size of the secondary particles formed by the agglomeration of the primary particles. In this application, the particle size specifically refers to the median particle size D50, i.e. DV50, which means the particle size corresponding to when the cumulative particle size distribution percentage of the measured sample reaches 50%. The physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%.

[0039] In an embodiment of the present application, the particle size of the lithium-supplementing particles 102 is 0.1μm-12μm. In some specific embodiments, the particle size of the lithium-supplementing particles 102 can be, for example, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.8μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 8μm, 10μm, 12μm. In some embodiments of the present application, the particle size of the lithium-supplementing particles 102 is 0.1μm-10μm. In some embodiments, the particle size of the lithium-supplementing particles 102 is 0.2μm-5μm. In an embodiment of the present application, the particle size of the lithium-supplementing particles 102 can be the particle size of the primary particles, or it can be the particle size of the secondary particles formed by the agglomeration of the primary particles. The commonly used lithium supplement agents usually have a large particle size, which is about one order of magnitude larger than the positive electrode active material, so that the lithium supplement agent particles shrink after the lithium supplement is decomposed, resulting in the formation of collapsed holes around the lithium supplement agent particles, which in turn causes the electrical contact between the positive electrode active materials in the positive electrode sheet to deteriorate. Compared with the conventional lithium supplement agent particles directly added to the positive electrode active slurry, the lithium supplement particles 102 of the present application have a particle size of about one order of magnitude smaller, which effectively shortens the migration path of lithium ions and enhances the ion transmission capacity of the lithium supplement positive electrode material; and effectively increases the interface area of ​​the lithium supplement particles, reducing the upper limit voltage of the lithium supplement particles during the first charge decomposition process. In addition, since the decomposition polarization of the lithium supplement particles is effectively alleviated during the first charge, the current density of the decomposition process is improved, which can effectively shorten the decomposition time of the lithium supplement particles, thereby not only reducing the side reactions caused by the high voltage environment, but also improving the production efficiency of the battery.

[0040] In the embodiment of the present application, the particle sizes of the active material core 101 and the lithium supplement particles 102 may be the same or different; the particle size of the active material core 101 may be larger than the particle size of the lithium supplement particles 102, or smaller than the particle size of the lithium supplement particles 102. The present application controls the particle sizes of the active material core and the lithium supplement particles within a suitable range, which is not only beneficial to the processing of the lithium supplement positive electrode material particles, but also beneficial to improving the processing stability of the slurry during the preparation of the slurry, thereby further improving the specific capacity and rate performance of the lithium supplement positive electrode material and further reducing the decomposition voltage.

[0041] In the embodiment of the present application, the specific surface area of ​​the lithium-supplementing positive electrode material 100 is 3 m 2 / g-20m 2 In some specific embodiments, the specific surface area of ​​the lithium-supplementing positive electrode material 100 may be, for example, 3 m 2 / g, 5m 2 / g, 6m 2 / g, 8m 2 / g, 10m 2 / g, 12m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 18m 2 / g, 20m 2 In some embodiments, the specific surface area of ​​the lithium-supplementing positive electrode material 100 may be 5 m 2 / g-18m 2 / g. The present application controls the particle size of the active material core and the lithium supplement particles within a suitable range and thus controls the specific surface area of ​​the lithium supplement positive electrode material within a suitable range, thereby further improving the stability of the lithium supplement positive electrode material and improving the cycle performance and service life of the battery.

[0042] The lithium-supplemented positive electrode material provided in the present application can effectively avoid the gelation of the positive electrode active slurry by specially designing its structure, in-situ compounding of the lithium-supplemented particles with the active material core and coating with carbon, and can improve the electronic and ion conductivity of the lithium-supplemented positive electrode material, and can also effectively slow down the rate of failure of the lithium-supplemented particles due to water absorption. In addition, the structure of the lithium-supplemented positive electrode material can also effectively reduce the decomposition voltage, thereby solving the gas production problem of the battery during later use, thereby improving the battery's cycle performance, service life and safety performance.

[0043] The present application also provides a method for preparing the lithium-supplemented positive electrode material provided above, comprising:

[0044] S101, mixing a lithium source, a phosphorus source, an iron source, a carbon source and an M metal source to obtain a lithium-supplementing positive electrode material precursor; or, mixing a lithium source, a phosphorus source, an iron source, a carbon source, a manganese source and an M metal source to obtain a lithium-supplementing positive electrode material precursor;

[0045] S102, sintering the lithium-supplementing positive electrode material precursor in stages to obtain a lithium-supplementing positive electrode material.

[0046] In step S101, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium hydroxide monohydrate, lithium nitrate, lithium oxide, lithium peroxide and lithium acetate; the phosphorus source includes one or more of lithium dihydrogen phosphate, ferric phosphate, ammonium phosphate, sodium dihydrogen phosphate, lithium monohydrogen phosphate, lithium phytate and sodium tripolyphosphate; the iron source includes one or more of ferrous oxide, ferric oxide, ferric nitrate, ferric phosphate, ferrous oxalate and ferrous sulfate; the carbon source includes one or more of sugars, high molecular organic matter and conductive carbon, and the carbon source specifically includes one or more of glucose, sucrose, fructose, chitosan, lignin, carboxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, phenolic resin, needle coke, petroleum coke, asphalt coke, asphalt, polystyrene, polyphenylene vinylene, carbon black, acetylene black, super-P, carbon nanotubes, graphene, ketjen black and vapor-grown carbon fiber; the manganese source includes one or more of manganese tetraoxide, manganese sulfate, manganese oxalate, manganese carbonate, manganese dioxide and manganese acetate.

[0047] In some embodiments of the present application, the raw materials for preparing the lithium - supplemented cathode material precursor include a lithium source, a phosphorus source, an iron source, a carbon source, and an M metal source. The active material core of the prepared lithium - supplemented cathode material is Li x Fe y PO4, where 0.9 ≤ x ≤ 1.1 and 0.9 ≤ y ≤ 1.1. In the embodiments of the present application, the feeding ratio of the lithium source, the phosphorus source, the iron source, the carbon source, and the M metal source is (1 - 1.2):(0.9 - 1.1):(0.9 - 1.1):(0.05 - 0.1):(0.01 - 0.05).

[0048] In other embodiments of the present application, the raw materials for preparing the lithium - supplemented cathode material precursor include a lithium source, a phosphorus source, an iron source, a carbon source, a manganese source, and an M metal source. The active material core of the prepared lithium - supplemented cathode material is LiFe z Mn 1-z PO4, where 0 < z < 1. In the embodiments of the present application, the feeding ratio of the lithium source, the phosphorus source, the iron source, the carbon source, the manganese source, and the M metal source is (1 - 1.2):(0.9 - 1.1):(0.4 - 0.6):(0.05 - 0.1):(0.4 - 0.6):(0.01 - 0.05).

[0049] In the embodiments of the present application, the M metal source is selected from one or more of an iron source, a manganese source, a nickel source, a zirconium source, a cobalt source, and a copper source. In the embodiments of the present application, the M metal source includes, but is not limited to, one or more of oxides, hydroxides, sulfates, and acetates of M.

[0050] In the embodiments of the present application, the mixing method includes, but is not limited to, ball - milling mixing.

[0051] In step S102, the segmented sintering sequentially includes a first sintering treatment and a second sintering treatment. In the embodiments of the present application, the sintering temperature of the first sintering treatment is 450°C - 750°C, and the sintering time is 3h - 18h. In some specific embodiments, the sintering temperature of the first sintering treatment can be, for example, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C; the sintering time can be, for example, 3h, 5h, 6h, 9h, 10h, 12h, 15h, 18h. By controlling the temperature and time of the first sintering treatment within a suitable range in the present application, the active material core particles can be prepared from the lithium source, the phosphorus source, and the iron source. In the embodiments of the present application, the first sintering treatment is carried out in a protective atmosphere, and the protective atmosphere includes, but is not limited to, a nitrogen atmosphere or an argon atmosphere. In the present application, the oxygen source of the active material core particles and the lithium - supplemented particles comes from at least one of the lithium source, the phosphorus source, the iron source, the carbon source, and the M metal source.

[0052] In the embodiment of the present application, the sintering temperature of the second sintering treatment is 750℃-1000℃, and the sintering time is 4h-36h. In some specific embodiments, the sintering temperature of the second sintering treatment can be, for example, 750℃, 800℃, 850℃, 900℃, 950℃, 1000℃; the sintering time can be, for example, 4h, 5h, 8h, 10h, 12h, 15h, 16h, 20h, 24h, 28h, 30h, 32h, 36h. The present application can in-situ composite lithium supplement particles on the basis of the prepared active material core particles by controlling the temperature and time of the second sintering treatment within a suitable range, and at this temperature, the carbon source plays a reducing role on the one hand, and can also obtain a carbon coating layer on the surface of the lithium supplement positive electrode material on the other hand. In some embodiments, the phosphorus source for preparing the active material core will be doped into the lithium supplement particles to obtain phosphorus-doped lithium supplement particles, which further reduces the polarization effect during the decomposition of the lithium supplement particles and further improves the conductivity and stability of the lithium supplement particles. In the embodiment of the present application, the second sintering process is performed under a protective atmosphere, and the protective atmosphere includes but is not limited to a nitrogen atmosphere or an argon atmosphere.

[0053] In the implementation mode of the present application, the temperature of the second sintering treatment is higher than the temperature of the first sintering treatment. The present application uses a two-stage segmented sintering to obtain a lithium-supplementing positive electrode material in which the surface-coated carbon-coated lithium-supplementing particles are in-situ composited with an active material core in the same sintering equipment, without the need to use two sets of sintering equipment, thereby reducing the cost of synthesizing lithium-supplementing particles. In the present application, the active material core can be formed first at the first sintering temperature, and the temperature is continued to be raised to the second sintering temperature, so that the lithium-supplementing particles and the carbon coating can be in-situ composited on the basis of the active material core.

[0054] In the embodiment of the present application, the lithium-supplemented positive electrode material prepared in step S102 may include: Figure 1 The lithium-supplemented positive electrode material 100 shown in FIG. Figure 2 In some specific embodiments, the lithium-supplementing positive electrode material prepared in step S102 may include one or more of the following: Figure 1 The lithium-supplemented positive electrode material 100 shown in FIG. Figure 2 The lithium-supplementing positive electrode material shown.

[0055] The preparation method of the lithium-replenishing positive electrode material provided in the present application controls the feed ratio of each raw material within an appropriate range, and obtains the lithium-replenishing positive electrode material in which the active material core is in situ composited with lithium-replenishing particles and coated with carbon through a two-stage sintering process. The size of the lithium-replenishing particles of the lithium-replenishing positive electrode material is much smaller than that of the conventional lithium-replenishing agent. The prepared lithium-replenishing positive electrode material has lower requirements on the feed and coating process of the positive electrode preparation and is not prone to gelation during the preparation of the slurry, which shortens the preparation process, reduces production costs and improves the preparation yield.

[0056] The present application also provides a positive electrode sheet, which includes a current collector and a positive electrode active layer loaded on the current collector, and the positive electrode active layer includes a lithium-supplementing positive electrode material as provided in the previous text of the present application or a lithium-supplementing positive electrode material prepared by the preparation method as provided in the previous text of the present application. In the embodiment of the present application, the positive electrode active layer also includes a binder and a conductive agent. In the embodiment of the present application, the conductive agent can be any conductive agent known in the art, including but not limited to one or more of super P-Li, superP, acetylene black, graphene and carbon nanotubes. In the embodiment of the present application, the binder can be any binder known in the art, including but not limited to polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyethylene oxide (PEO) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and the like.

[0057] The present application also provides a lithium-ion battery, which includes a positive electrode sheet, a negative electrode sheet, and a separator and an electrolyte located between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet includes a positive electrode sheet as provided in the previous text of the present application. In the embodiment of the present application, the separator includes but is not limited to a polymer film. In the embodiment of the present application, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on the negative electrode current collector, and the negative electrode active material in the negative electrode material layer can be any negative electrode active material for lithium-ion batteries known in the art. In the embodiment of the present application, the negative electrode active material in the negative electrode material layer can be any negative electrode active material for lithium-ion batteries known in the art. Exemplarily, the negative electrode active material can be selected from one or more of carbon-based negative electrode active materials, silicon-based negative electrode active materials, tin-based negative electrode active materials, and lithium metal negative electrode active materials. Among them, the carbon-based negative electrode includes but is not limited to natural graphite, artificial graphite, hard carbon, soft carbon, and graphene; the silicon-based negative electrode includes but is not limited to silicon, silicon carbon, silicon oxygen, etc.; the tin-based negative electrode includes but is not limited to tin, tin carbon, tin oxygen, and tin metal compounds.

[0058] The present application also provides an electrical device, which includes the lithium-ion battery described above. The electrical device may be, for example, an electric car, a mobile phone, a tablet computer, a laptop computer, a wearable device (a watch, a bracelet), a digital camera, etc.

[0059] The present application is further described below in multiple embodiments:

[0060] Example 1

[0061] Weigh lithium carbonate, iron phosphate, ferric oxide and glucose in a molar ratio of 1.1:2:0.02:0.05, and mix them to obtain a lithium-supplementing positive electrode material precursor;

[0062] The obtained lithium-supplementing positive electrode material precursor is subjected to staged sintering, firstly, a first sintering treatment is carried out at 650° C. for 12 h, and then a second sintering treatment is carried out at 850° C. for 8 h, to obtain a lithium-supplementing positive electrode material;

[0063] The prepared lithium-replenishing positive electrode material is dissolved in N-methylpyrrolidone solvent to prepare positive electrode slurry, and the obtained positive electrode slurry is evenly coated on aluminum foil and vacuum dried to obtain a lithium-replenishing positive electrode sheet.

[0064] Example 2

[0065] The difference from Example 1 is that the raw materials of the lithium-supplementing positive electrode material precursor are lithium carbonate, iron phosphate, cobalt oxide and glucose in a molar ratio of 1.12:2:0.02:0.05.

[0066] Example 3

[0067] The difference from Example 1 is that the raw materials of the lithium-supplementing positive electrode material precursor are lithium carbonate, iron phosphate, copper oxide and glucose in a molar ratio of 1.05:2:0.05:0.05.

[0068] Example 4

[0069] The difference from Example 1 is that the raw materials of the lithium-supplementing positive electrode material precursor are lithium carbonate, iron phosphate, manganese phosphate, ferric oxide and glucose in a molar ratio of 1.1:0.8:1.2:0.02:0.08.

[0070] Example 5

[0071] The difference from Example 1 is that the molar ratio of lithium carbonate, ferric phosphate, ferric oxide and glucose is 1.2:2:0.04:0.05.

[0072] Example 6

[0073] The difference from Example 1 is that the molar ratio of lithium carbonate, ferric phosphate, ferric oxide and glucose is 1.05:2:0.01:0.05.

[0074] Example 7

[0075] The difference from Example 1 is that the temperature of the first sintering treatment is 600° C. and the time is 8 hours; the temperature of the second sintering treatment is 900° C. and the time is 4 hours.

[0076] Comparative Example 1

[0077] Weigh 100 parts by weight of active material lithium iron phosphate and dissolve it in N-methylpyrrolidone solvent to prepare lithium iron phosphate slurry, then weigh 2 parts by weight of lithium supplement agent Li5FeO4 and add it to the lithium iron phosphate slurry, stir evenly to obtain positive electrode slurry, evenly apply the obtained positive electrode slurry on aluminum foil and vacuum dry it to obtain a lithium supplement positive electrode sheet.

[0078] Performance Testing

[0079] Specific surface area: The lithium-supplemented positive electrode materials of Examples 1 to 7 were tested according to the national standard "Determination of Specific Surface Area of ​​Solid Materials by Gas Adsorption BET Method" (GB / T 19587-2017) to measure their specific surface areas. The results are shown in Table 1.

[0080] Particle size Dv50: The particle sizes of the active material cores and lithium supplement particles of Examples 1 to 7 and the active material of Comparative Example 1 were tested using a laser particle size distribution analyzer. The measured particle sizes Dv50 are shown in Table 1.

[0081] The lithium-supplemented positive electrode plates and negative electrodes, separators, and electrolytes prepared in Examples 1 to 7 and Comparative Example 1 are converted into soft-pack batteries.

[0082] Gas production performance: The SOC of the soft-pack batteries prepared in Examples 1 to 7 and Comparative Example 1 was adjusted to 100%, 90%, 80%, 70%, 60%, 50%, 40%, 30%, 20%, 10%, and 0% in turn. After being stored at 60°C for 28 days, the battery weight was tested by the drainage method. The gas production performance of the battery was calculated and statistically analyzed by the weight difference. The results are shown in Table 1.

[0083] Cycle performance: The soft-pack batteries prepared in Examples 1 to 7 and Comparative Example 1 were charged at 45°C with a cutoff current of 0.05C from 0.5CCC-CV to 3.7V and discharged at 0.5C to 2.3V. After 1000 cycles, the retention rate of the battery capacity relative to the battery capacity before the cycle was checked. The results are shown in Table 1.

[0084] Rate performance: The soft-pack batteries prepared in Examples 1 to 7 and Comparative Example 1 were charged at 25°C with a cutoff current of 0.05C from 0.5C CC-CV to 3.7V and discharged at 0.1C to 2.3V, and the capacity was recorded as C1; at 25°C, the cutoff current of 0.05C from 0.5C CC-CV to 3.7V and discharged at 2C to 2.3V were recorded as C2; the calculation formula for the 2C / 0.1C capacity retention rate was: C2 / C1*100%, and the results are shown in Table 1.

[0085] Table 1

[0086]

[0087] It can be seen from Table 1 that compared with Comparative Example 1 in which lithium-replenishing particles are directly added to the active slurry, Examples 1 to 7 of the present application significantly reduce the particle size of the lithium-replenishing particles by in-situ composite lithium-replenishing particles in the core of the positive electrode active material and coating them with carbon materials, effectively reduce the risk of gelation of the positive electrode active slurry caused by residual alkali on the surface of the lithium-replenishing particles, and can improve the electronic conductivity and ion conductivity of the lithium-replenishing positive electrode material, and also reduce its decomposition voltage, reduce the gas production of the battery, and thereby improve the cycle performance and rate performance of the battery.

[0088] The preferred embodiments are described in detail above, but the present invention is not limited to the above-mentioned specific implementation modes. Under the guidance of the present application, technicians in this field can also make various specific changes without departing from the scope of protection of the present application, which all fall within the scope of protection of the present invention.

Claims

1. A lithium-supplementing positive electrode material, characterized in that: The lithium - supplemented cathode material includes an active material core and a coating layer coated on the surface of the active material core. The coating layer includes lithium - supplemented particles and carbon. The active material core includes one or more of Li x Fe y PO4 and LiFe z Mn 1-z PO4, where 0.9 ≤ x ≤ 1.1, 0.9 ≤ y ≤ 1.1, 0 < z < 1. The lithium - supplemented particles include Li a M b O c , where M is selected from one or more of Fe, Mn, Ni, Zr, Co, Cr, and Cu, 0 < a ≤ 6, 0 < b ≤ 3, 0 < c ≤ 5.

2. The lithium-supplementing positive electrode material according to claim 1, characterized in that: The carbon is coated on the surface of the active material core and / or the surface of the lithium supplement particle.

3. The lithium-supplementing positive electrode material according to claim 1 or 2, characterized in that: At least part of the lithium-supplementing particles are in-situ grown on the surface of the active material core.

4. The lithium-supplementing positive electrode material according to any one of claims 1 to 3, characterized in that: The mass ratio of the lithium supplement particles to the active material core is (0.1-10):

100.

5. The lithium-supplementing positive electrode material according to any one of claims 1 to 4, characterized in that: The mass percentage of the carbon in the lithium-supplementing positive electrode material is 0.1%-5%.

6. The lithium-supplementing positive electrode material according to any one of claims 1 to 5, characterized in that: The particle size of the active material core is 0.1 μm-15 μm; the particle size of the lithium supplement particle is 0.1 μm-12 μm.

7. The lithium-supplementing positive electrode material according to any one of claims 1 to 6, characterized in that: The specific surface area of ​​the lithium-supplementing positive electrode material is 3 m 2 / g-20m 2 / g.

8. A method for preparing the lithium-supplemented positive electrode material according to any one of claims 1 to 7, characterized in that: include: Mixing a lithium source, a phosphorus source, an iron source, a carbon source and an M metal source to obtain a lithium-supplementing positive electrode material precursor; Or, a lithium source, a phosphorus source, an iron source, a carbon source, a manganese source and an M metal source are mixed to obtain a lithium-supplementing positive electrode material precursor; The lithium-supplementing positive electrode material precursor is sintered in stages to obtain the lithium-supplementing positive electrode material.

9. The method for preparing a lithium-supplemented positive electrode material according to claim 8, characterized in that: The staged sintering includes a first sintering treatment and a second sintering treatment performed sequentially; the sintering temperature of the first sintering treatment is 450°C-750°C, and the sintering time is 3h-18h; the sintering temperature of the second sintering treatment is 750°C-1000°C, and the sintering time is 4h-36h; the temperature of the second sintering treatment is higher than the temperature of the first sintering treatment.

10. The method for preparing a lithium-supplemented positive electrode material according to claim 8 or 9, characterized in that: The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium hydroxide monohydrate, lithium nitrate, lithium oxide, lithium peroxide and lithium acetate; The phosphorus source includes one or more of lithium dihydrogen phosphate, iron phosphate, ammonium phosphate, sodium dihydrogen phosphate, lithium monohydrogen phosphate, lithium phytate and sodium tripolyphosphate; The iron source includes one or more of ferrous oxide, ferrous oxide, ferric nitrate, ferric phosphate, ferrous oxalate and ferrous sulfate; The carbon source includes one or more of sugars, high molecular organic matter, and conductive carbon, and the carbon source specifically includes one or more of glucose, sucrose, fructose, chitosan, lignin, carboxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, phenolic resin, needle coke, petroleum coke, pitch coke, asphalt, polystyrene, polyphenylene vinylene, carbon black, acetylene black, super-P, carbon nanotubes, graphene, Ketjen black, and vapor-grown carbon fiber; The manganese source includes one or more of manganese tetraoxide, manganese sulfate, manganese oxalate, manganese carbonate, manganese dioxide and manganese acetate.

11. A positive electrode sheet, characterized in that: The positive electrode sheet includes a current collector and a positive electrode active layer loaded on the current collector, and the positive electrode active layer includes the lithium-supplementing positive electrode material according to any one of claims 1 to 7 or the lithium-supplementing positive electrode material prepared by the preparation method according to any one of claims 8 to 10.

12. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 11.

13. An electrical equipment, characterized in that: The electrical device comprises the lithium-ion battery as claimed in claim 12.

Citation Information

Patent Citations

  • In-situ lithium supplementing method for lithium ion battery positive electrode material

    CN111769288A

  • Lithium self-supplementing type ternary material, preparation method and application

    CN116845191A

  • Composite positive electrode material and preparation method thereof, positive electrode plate and secondary battery

    CN117334909A

  • Composite positive electrode material and preparation method and application thereof

    CN117894945A

  • Method for producing lithium-based polyanion particle composite for lithium ion secondary battery positive electrode active material

    JP2024113763A

Cited By

  • Composite lithium supplement agent and preparation method and application thereof

    CN119921006A

  • A composite lithium supplement agent, its preparation method and application

    CN119921006B

  • Composite lithium supplement additive and preparation method and application thereof

    CN120048890A

  • High-rate lithium ferric manganese phosphate material as well as preparation method and application thereof

    CN120504304A

  • Lithium-supplementing positive electrode material, and preparation method therefor and use thereof

    WO2026065928A1